TEORIA DISCURSULUI: APLICABILITATE ÎN ANALIZA SCHIMBĂRILOR DE PARADIGMĂ ÎN STUDIILE DE SECURITATE - Robert-Ionuț STANCIU (Intelligence și Cultura de Securitate)
This article examines discourse theories, its components (tools or manifestations) and their applicability in security studies. Starting from the generic framing of discourse theories in social sciences, the research aims to particularize and niche the attention towards causal links, and specific markers, which can be used methodologically to identify a paradigm shift in security studies. In this context, the research was based on the following questions: What is discourse theory? What are the tools of discourse theory? How can these act as a litmus in revealing a paradigm shift in security studies? The methodology used was the transversal analysis of discourse theories and its relevance in security studies. Process tracing and document analysis techniques were also used to determine causality effects between speeches and security postures. The main findings of the research reveal that discourse theory is an important tool for understanding the way in which language can be used to influence beliefs, social and political attitudes, but also for the transmission of warning messages regarding a change of position in addressing security and defense. Discourse theory also offers insights into how language can be used to maintain existing power structures. The assertion applies equally to both social groups and entities that are part of the international security system (states, organizations, institutions, etc.). Using language in specific ways can influence institutional behavior in a manner favorable to the sender, provided that the promoters of the messages are referential authorities called hegemonic agents. Based on these benchmarks, we believe and prove that the use of methodological language/speech analysis mechanisms could provide a priori relevant information regarding intentions, objectives and positions that the issuer can adopt. All this could contribute to the (pre)notification of an implicit or explicit paradigmatic change.